Rock - paper - pixels : how our need to communicate created a new economy, society, and individual : what will be the effects of artificial intelligence and quantum computing - Aievoli, Patrick (Boca Raton ; London ; New York : CRC Press : Taylor & Francis Group, 2025)
The purpose of this book is to avail students of the many different reasons and back-stories equated with the advent of interaction design and its effect on our world. Since the beginning of recorded history, humankind has desired to keep track of its events and accoumplishments and to find a way to properly represent those occurrences to the rest of the world. Now with the use of interaction design and new technologies it has become possible to present the story through current and diverse platforms. As the new generation comes of age, a new method is being utilized in all areas of communication. This new generation - Generation i - desires its communication at a different rate than its predecessors. This new Gen-i wants its information Internet-ready and interactive. This generation has become involved in the immediate and it is not going away. Interactive media is here to stay - from the halls of famous museums to the conference rooms of corporations to the entertainment centers in our homes. A new vision of information distribution has taken root. The main goal of this book is to help you take your best steps in that new direction To help you understand the effects of this new platform and to be aware of its abilities and its dangers. As a friend once said, "no matter how thin you slice it, there are always two sides."
Obsahuje profesijné údaje o autorovi
Obsahuje bibliografiu a register
Študentom
Keywords: interpersonálna komunikácia; Interpersonal communication; ekonómia; Economy; spoločnosť; Sciety; umelá inteligencia; Artificial intelligence; kvantové počítače; Quantum computers; monografie; Monographs